Oxford english for careers Medicine 2 : Student's Book / Sam McCarter - McCarter, Sam
English for Careers is a series which prepares pre-work students for starting their career. Everything in each Student’s Book is vocation-specific, which means students get the language, information, and skills they need to help them get a job in their chosen career. A specialist course for medical students, doctors, and advanced nurses who want to work in English-speaking countries. Medicine has been designed to help students communicate accurately in English with patients and colleagues. It has a clear focus on developing speaking and listening skills for a range of different situations. Key features: